2013
DOI: 10.1371/journal.ppat.1003748
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Host Activation-Induced Cytidine Deaminase in Innate Immune Defense against KSHV

Abstract: Activation-induced cytidine deaminase (AID) is specifically induced in germinal center B cells to carry out somatic hypermutation and class-switch recombination, two processes responsible for antibody diversification. Because of its mutagenic potential, AID expression and activity are tightly regulated to minimize unwanted DNA damage. Surprisingly, AID expression has been observed ectopically during pathogenic infections. However, the function of AID outside of the germinal centers remains largely uncharacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 85 publications
2
50
0
Order By: Relevance
“…However, HSV-1 reactivation was measured post-explant from trigeminal ganglia: a tissue composed of terminally differentiated adult neurons with low levels of host UNG (18,36). Reactivation is also reduced in human gammaherpesvirus latency cell systems lacking the EBV viral UNG (BKRF3) alone or in the absence of both the vUNG and the host UNG (13,18,(37)(38)(39). Interestingly, Su et al (13) recently reported that host UNG2 levels decrease as EBV reactivation proceeds, indicating that the viral UNG is needed to promote replication under conditions of low host UNG levels (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HSV-1 reactivation was measured post-explant from trigeminal ganglia: a tissue composed of terminally differentiated adult neurons with low levels of host UNG (18,36). Reactivation is also reduced in human gammaherpesvirus latency cell systems lacking the EBV viral UNG (BKRF3) alone or in the absence of both the vUNG and the host UNG (13,18,(37)(38)(39). Interestingly, Su et al (13) recently reported that host UNG2 levels decrease as EBV reactivation proceeds, indicating that the viral UNG is needed to promote replication under conditions of low host UNG levels (13).…”
Section: Discussionmentioning
confidence: 99%
“…This implicates a possible role for the vUNG in impacting B cell processes critical for gammaherpesvirus pathogenesis. Alternatively, given that gammaherpesviruses target B cells that undergo isotype-class switching and, in some reports, upregulate the B cell specific host cytidine deaminase, AID (39,43), it is possible that mutagenic effects of AID may exert a selective pressure that must be countered by the vUNG. Indeed, overexpression of AID impairs reactivation in KSHV-positive latent BCBL cell lines, and this defect is exacerbated with depletion of host UNG2 (39).…”
Section: Discussionmentioning
confidence: 99%
“…The KSHV-infected cell presents antigenic peptides from the virus in complex with MHC class I to cytotoxic T lymphocytes (CTLs) (64)(65)(66). Additionally, KSHV-infected B cells stimulate activation-induced cytidine deaminase (AID) expression and are targeted for elimination by NK cells through upregulation of NKG2D ligands (67). KSHV also encodes genes that inhibit these immune responses.…”
Section: Latent Kshv Infection and Reactivationmentioning
confidence: 99%
“…Meanwhile, host restriction factors inhibit KSHV infection by activating immune responses. KSHV infection of human primary naïve B cells induces rapid activation-induced cytidine deaminase (AID) expression, which plays a role in the innate immune defense against KSHV (29).…”
mentioning
confidence: 99%